Harmonics Reduction in a Current Source Fed Quasi-Resonant Inverter Based Induction Heater - Avijit Chakraborty; Titas Kumar Nag; Pradip Kumar Sadhu; Nitai Pal (Institute of Advanced Engineering and Science, 2016)
This paper investigates an approach to reduce the injection of unwanted harmonics from the input side power source. The proposed work finds an application of a suitably designed Low Pass Filter (LPF) for harmonics reduction. The Low Pass Filter is incorporated in between the input power source and high frequency current source fed single switch parallel quasi-resonant inverter of a domestic Induction Heater. The inverter has an Insulated Gate Bipolar Junction Transistor (IGBT) switch. Undesirable harmonics injection to the input power source makes voltage and current waveforms non-sinusoidal. Fast Fourier Transform (FFT) analysis has been applied to study the effect of harmonics in frequency domain. The entire system is realized in Power System Simulator (PSIM) environment. It is finally proved that the proposed filter reduces the Total Harmonic Distortion (THD) and the Distortion Factor (DF) of the input current. It is also proved that the proposed Low Pass Filter can make the input power factor closer to unity.